Home » Blog » Use differential equations to estimate the maximum population given census data

Use differential equations to estimate the maximum population given census data

From the previous exercise we have the following population growth law:

    \[ x = \frac{M}{1+e^{-a(t-t_1)}}. \]

Census data is taken at equally spaced times t_1, t_2, t_3 and the population at these times is given by x_1, x_2, x_3, respectively. Prove that this data is sufficient to determine the value of the constant M and that

    \[ M = x_2 \frac{x_3(x_2 - x_1) -x_1(x_3 - x_2)}{x_2^2 - x_1x_3}. \]


Proof. First, we use x(t_1) = x_1 to solve for t_0:

    \begin{align*}  x_1 = \frac{M}{1+e^{-\alpha(t_1-t_0)}} && \implies && e^{\alpha(t_1 - t_0)} &= \frac{x_1}{M-x_1} \\[9pt]  && \implies && t_0 &= t_1 - \left( \frac{1}{\alpha} \right) \log \left( \frac{x_1}{M-x_1} \right). \end{align*}

Then, substituting into x(t_2) = x_2:

    \begin{align*}  x_2 = \frac{M}{1+e^{-\alpha(t_2-t_0)}} && \implies && M &= x_2 + x_2 e^{-\alpha \left( t_2 - t_1 + \frac{1}{\alpha} \log \left( \frac{x_1}{M-x_1} \right) \right)} \\[9pt]  && \implies && M &= x_2 + x_2 e^{-\alpha(t_2-t_1)} \cdot \frac{M-x_1}{x_1} \\[9pt]  && \implies && \frac{Mx_1 - x_1 x_2}{M-x_1} &= x_2 e^{-\alpha(t_2 - t_1)}. \end{align*}

Since t_1, t_2, t_3 are equally spaced by assumption, we have t_2 - t_1 = t_3 - t_2 = 2 (t_3 - t_1). Therefore,

    \[ e^{-\alpha(t_3-t_1)} = \left( \frac{x_1 (M-x_1)}{x_2 (M-x_2)} \right)^2. \]

Finally, using x(t_3) = x_3, we have,

    \begin{align*}  &&x_3 &= \frac{M}{1 + e^{-\alpha(t_3 - t_0)}} \\[9pt]  \implies && M &= x_3 + x_3 e^{-\alpha \left( t_3 - t_1 + \frac{1}{\alpha} \log \left( \frac{x_1}{M-x_1} \right) \right)} \\[9pt]  \implies && M &= x_3 + x_3 e^{-\alpha (t_3 -t_1)} \cdot \left( \frac{M-x_1}{x_1} \right) \\[9pt]  \implies && M &= x_3 + x_3 \left( \frac{x_1 (M-x_2)}{x_2 (M-x_1)} \right)^2 \cdot \left( \frac{M-x_1}{x_1} \right) \\[9pt]  \implies && M&= x_3 + \frac{x_1 x_3 (M-x_2)^2}{x_2^2 (M-x_1)} \\[9pt]  \implies && M (M-x_1) &= \left( \frac{1}{x_2^2} \right) \left( Mx_3 x_2^2 - x_1 x_3 x_2^2 + M^2 x_1 x_3 - 2M x_1 x_2 x_3 + x_1 x_3 x_2^2 \right) \\[9pt]  \implies && Mx_2^2 - x_1 x_2^2 &= x_3 x_2^2 + Mx_1 x_3 - 2x_1 x_2 x_3 \\[9pt]  \implies && M(x_2^2 - x_1 x_3) &= x_2 (x_3 x_2 - x_1 x_3 + x_1 x_2 - x_1 x_3) \\[9pt]  \implies && M &= x_2 \cdot \frac{x_3 (x_2 - x_1) - x_1 (x_3 - x_2)}{x_2^2 - x_1 x_3}. \qquad \blacksquare \end{align*}

Point out an error, ask a question, offer an alternative solution (to use Latex type [latexpage] at the top of your comment):